The Relationship of Painful and Pleasant Childhood Experiences With Self Esteem In Physical Education Students/ University of Mostanseria - Abdul Wahid, Amira (Journal of Physical Education, 2016)
The importance of the research lies in the youth that are considered national treasure for developing the country and its culture. The problem of the research was in discovering the relationship between childhood experiences and self esteem in third year students and using these experiences for positive psychological personality building. The researchers hypothesized statistical differences between pleasant and painful childhood experiences with self – esteem in third year students. The researchers used the scanning method. The subjects were (70) third year students selected randomly. Childhood experiences scale was applied. The scale consisted of 86 item (48) of them measure painful childhood experiences while 38 items measure pleasant experiences. The self – esteem scale was also used it consisted of 62 items. The researchers concluded that there are significant differences between pleasant childhood experiences and self esteem. In addition to that, they concluded the lack of differences between painful childhood experiences and self esteem in third year students. The researchers recommended making awareness programs for students in order to gain new pleasant experiences that help them improve their positive self – esteem.